Quality of Work Life as a Correlate of Sustainable Employee Performance in Health Institutions in Owerri (West African Journal on Sustainable Development, 2024)
Employees normally do better at the workplace when they are touched at the points of their needs. This study investigates Quality of Work Life (QWL) as a correlate of employee performance in health institutions in Owerri. The objectives of the study are to examine the level of correlation between fair compensation and employee commitment; examine the level of correlation between fair compensation and adherence to ethical standards; evaluate the level of correlation between employee participation and employee commitment; and assess the level of correlation between employee participation and adherence to ethical standards. The researchers developed a problem statement that captured the research gaps which called for the study. The study was guided by four research questions and four hypotheses. The research adopts the Ken-C theory of Social Honour for the theoretical framework. It uses various empirical reviews to enrich the work. The study employs the survey research design. A structured questionnaire constitutes the major instrument for data collection. It uses Cronbach Alpha statistic for obtaining 0.84 as the reliability ratio of the survey instrument. The research commits data analysis to descriptive statistics. It employs Spearman Product Moment Correlation Coefficient for testing hypotheses. The study finds that each of the indices of QWL namely fair compensation and employee participation positively and significantly improved the indices of employee performance namely employee commitment and adherence to ethical standards in the health institutions. It was concluded that QWL is a correlate of employee performance in health institutions in Owerri. The paper recommends that the management of health institutions should always offer workers handsome salaries, good wages and fringe benefits for improved employee performance. Workers should be allowed to participate in decision making for sound employee performance outcomes especially employee commitment and improved ethical standards.
Keywords: Quality of Work Life; Employee performance; Health institutions